(untitled) (SCIÉNDO INGENIUM, 2024)
The objective of the research was to determine the % impact of urban demographic expansion on environmental sustainability in Nuevo Chimbote, for the research, the district was divided into two zones, consolidated and expansion, the method used was observational and the experimental design was descriptive-relational, to estimate the sample size, the mathematical model for a finite population with categorical variables was used. The sampling was two-stage, to collect data, the observational and documentary techniques were used, in the latter the questionnaire and the interview guide were used as instruments, validated by experts, then the statistical analysis was done to check the relationship between the variables. The migratory dynamic brings with it the appearance of new towns as a consequence of invasions, generating deficiencies in basic services, overcrowding, an increase in household and construction waste, the loss of green areas, and biodiversity, adding the scarce environmental culture, the lack of treatment of household waste, the non-reuse of construction waste and disorganized population growth. It is concluded that urban demographic expansion negatively affects the environmental sustainability of the district, which according to the statistical analysis showed a value of p < 0.05.